Odbicie społecznej nauki Kościoła katolickiego w programach głównych stronnictw politycznych II Rzeczypospolitej - Krukowski, Stanisław (Prawo Kanoniczne, 1987)
The „Rerum novarum” encyclical, enacted in 1891 by pope Leon XIII significantly contributed to the rapid development of the Catholic social science. The next, important stage of that development was marked in 1931 by the encyclical of pope Pius XI. Catholic social thought was considerably developed in Poland at the time of the Second Republic by such prominent priests as: Antoni Szymański, Aleksander Wójcicki, Jan Piwowarczyk and Stefan Wyszyński — later cardinal and Primate of Poland. Some representatives of the Church’s hierarchy, like August cardinal Hlond, Primate of Poland, bishop Stanisław Adamski of Katowice and bishop Teodor Kubina of Częstochowa have also made an important contribution to the development of the Catholic church social science in Poland. At the same time in Poland — like in other countries — many different Catholic-social organizations were created, including political parties like Christian-Democracy and Labour Party. These parties, however, were not among the strongest ones in the Republic. The Catholic social science was fully incorporated — sometimes even developed — in their programs, but their possibilities to put these ideas into political action were much more limited. Some particular elements of social-Catholic thought appeared in programs of many political groups of the Second Republic, but often that was coincidence rather, than fully conscious choice of social Catholicism principles.